68Ga-DOTATATE PET/CT Findings of Cervical Esophageal Neuroendocrine Tumor - (:unkn) unknown (Lippincott Williams and Wilkins, 2021)
Neuroendocrine tumors (NETs) of the esophagus are extremely rare and aggressive and have a poor prognosis. Because most esophageal cancers occur in the middle and lower parts of the esophagus, cervical esophageal NETs are even rarer. Herein, we present 68Ga-DOTATATE PET/CT findings in a 37-year-old woman who was diagnosed with cervical esophageal NET. © Wolters Kluwer Health, Inc. All rights reserved.
Keywords: DOTATATE; esophagus; neuroendocrine tumor; PET/CT